THE USE OF DIFFERENT OYSTER MUSHROOM BAGLOG WASTE AND RICE BRAN ON MAGGOT PRODUCTION AND BIOCONVERSION VALUE - Muhammad Ikhsan Solehin; Neni Widaningsih; Muhammad Irwan Zakir (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The purpose of this study was to analyze the effect of using oyster mushroom baglog waste and rice bran on the production yield and bioconversion value of maggot. The design used was a fully randomized design (RAL) with 5 treatments and 4 replications, namely P1 = 100% oyster mushroom baglog waste; P2 = 75% oyster mushroom baglog waste + 25% rice bran; P3 = 50% oyster mushroom baglog waste + 50% rice bran; P4 = 25% oyster mushroom baglog waste + 75% rice bran; and P5 = 100% rice bran. The variables observed in this study were maggot production and maggot bioconversion value. The data obtained were analyzed using analysis of variance (ANOVA) and if the results obtained showed a significant effect, then continued with the Duncan Multiple Range Test. The results showed that the use of oyster mushroom baglog waste and rice bran affected the production and bioconversion value of maggot. The use of 25% oyster mushroom baglog waste and 75% rice bran gave the highest results with an average maggot production of 90.75 grams and a bioconversion value of 6.48%.